PUTTING QUANTUM MEDICINE TO THE TEST: A CRITICAL ANALYSIS OF EVIDENCE - Petrova, Anya; Ahmed, Omar (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Quantum medicine offers a holistic approach to health and well-being, addressing all the senses and their associated discomfort. This emerging field not only encompasses preventive measures but also extends its healing potential to conditions where pain has already manifested. The comprehensive nature of quantum medicine allows for the incorporation of various medical specialties, making it a potentially transformative area of medicine. One of the fundamental aspects of quantum medicine is its association with quantum physics, which deals with physical systems and phenomena at the atomic and subatomic scale. This contrast with classical physics has led to a deeper understanding of the underlying principles governing these intricate systems. However, the exact mechanisms by which quantum medicine achieves its healing effects remain elusive, as they involve microparticles, atoms, electrons, and protons operating on an atomic scale. This abstract piques interest in the potential of quantum medicine but emphasizes the need for further research to unveil the specific energies and processes responsible for its therapeutic outcomes.